Pengaruh Citra Merek terhadap Keputusan Pembelian (Studi Produk Cimory Yoghurt di Alfamart Mekar Wangi) - Afreal Syahruliyanto; Prihartono Prihartono (Universitas Batanghari Jambi, 2022)
Cimory is a well-known yogurt brand in Indonesia, consumed by various groups, making this yogurt brand the main choice when consuming yogurt. This is evidenced by the Top Brand Award Indonesia 2020 in the fermented milk category, Cimory brand ranks first with an index of 69.6%, followed by Heavenly Blush brand in second place with an index of 13.9%, and 10.4% for Nutriboost. This study aims to determine the effect of brand image on Cimory yogurt purchasing decisions by applying 4 dimensions of brand image, namely brand identity, brand personality, brand association, and brand benefit and competence. The population in this study was 266 families in the coverage area at Alfamart Mekar Wangi and the sample was taken based on calculations using the slovin formula, namely, 73 respondents answered a questionnaire with 21 questions. The results of the study prove that the brand image variable has a significant influence on purchasing decisions with a value on hypothesis testing of 14.621 > t table 1.994. Output R Square of 75.1% (0.751) the data shows that purchasing decisions are influenced by brand image while the remaining 24.9% is on other variables not tested in this study.